Thoughts and best practices on the personal pages in the academic webspace - Aguillo, Isidro F. (Anuario ThinkEPI, 2010)
The Web is an important source of information in the academic sector, although many professors and researchers still do not maximize its potential. Missing or poor content is especially common on many personal or group sites. We propose a model with large and diverse content, strongly interlinked to represent the author´s network of contacts and experiences, and with a statistics system to monitor the number of visits and visitors. These pages can be complemented with Web 2.0 tools, but always subordinated to the personal page contents.